Possible links with methane seepage and gas hydrate dynamics inferred from authigenic barite records in the northern south china sea - Feng, Junxi; Luo, Min; Liang, Jinqiang; Yang, Shengxiong; Wang, Hongbin; Li, Niu; Sun, Xiaoming (Frontiers in Earth Science, 2022)
Numerous methane seepage events occurred in periods of low or falling sea level since 330 ka BP, which is attributed to decrease in hydrostatic pressure and subsequent gas hydrate dissociation in the northern South China Sea (SCS). The seepage intensity likely decrease due to gas hydrate stabilization once there was a relatively high-stand sea level. However, there are few geochemical records of decline in upward methane flux in the northern SCS. Here, combing porewater and solid-phase analyses, the geochemical cycling of barium was investigated in two piston cores from sites HD109 and HD319 within two areas with inferred gas hydrate occurrence in the Taixinan Basin of the northern SCS, in order to track the net decrease in the upward methane flux and to estimate the total duration time of these events in the studied sediments. The results indicate that there are four intervals with barium enrichments in the sediment section overlying the occurrent sulfate-methane transition zone (SMTZ) at both cores, suggesting the SMTZs have downward migrated through time. Based on the excess barium contents and the diffusive Ba2+ fluxes above the current SMTZ, we estimate the total time for barium accumulation at both cores is about ten thousand years. It is suggested that some methane seepage events temporarily enhance the upward flux of methane, inducing anaerobic oxidation of methane and associated SMTZ close to the sediment surface before the Holocene. After the most intensive seepage event ceased in the post-glacial period, the upward methane flux decreased and the SMTZ migrated downward gradually, preserving enrichments of diagenetic barite. Overall, these new data confirm the episodic decrease in upward methane flux recorded by authigenic barite after the last glacial maximum, which is likely related to the stabilization of underlying gas hydrate reservoir. This study may fill in the gap of the geochemical records of the variations in methane seepage and gas hydrate system during the post-glacial period in the northern SCS.